Direct U-series analysis of the Lezetxiki humerus reveals a Middle Pleistocene age for human remains in the Basque Country (northern Iberia). Issue 93 (April 2016) - de-la-Rúa, Concepción; Altuna, Jesús; Hervella, Monserrat; Kinsley, Leslie; Grün, Rainer
Abstract: In 1964, a human humerus was found in a sedimentary deposit in Lezetxiki Cave (Basque Country, northern Iberia). The first studies on the stratigraphy, associated mammal faunal remains and lithic implements placed the deposits containing the humerus into the Riss glacial stage. Direct chronometric evidence has so far been missing, and the previous chronostratigraphic framework and faunal dating gave inconsistent results. Here we report laser ablation U-series analyses on the humerus yielding a minimum age of 164 ± 9 ka, corresponding to MIS 6. This is the only direct dating analysis of the Lezetxiki humerus and confirms a Middle Pleistocene age for this hominin fossil. Morphometric analyses suggest that the Lezetxiki humerus has close affinities to other Middle Pleistocene archaic hominins, such as those from La Sima de los Huesos at Atapuerca. This emphasizes the significance of the Lezetxiki fossil within the populations that predate the Neanderthals in south-western Europe. It is thus an important key fossil for the understanding of human evolution in Europe during the Middle Pleistocene, a time period when a great morphological diversity is observed but whose phylogenetic meaning is not yet fully understood.